Advanced Patterning: Tackling the big problems in printing small features - Eynon, Benjamin G. (Proceedings of the IEEE International Interconnect Technology Conference, 2025)
The dramatic rise in demand for AI capability coupled with its ever-increasing hunger for the most advanced semiconductor devices, make the chances of achieving the forecasted 1trillion semiconductor industry value by 2030 look more plausible than ever. However, achieving perfect device functionality and high yield requires that semiconductor manufacturing process technologies all work in concert with one another at the angstrom scale. The search for ways and means to manufacture such incredibly complex devices at high yield has led the semiconductor industry to look its advanced patterning toolbox once again for answers.